1987
DOI: 10.2172/6158948
|View full text |Cite
|
Sign up to set email alerts
|

Fast current ramp experiments on TFTR

Abstract: This tep:tri was prepared ;is .in account of wi-rk sponsored h> :in ^jjeney of the United Slates tJuuTninjni. Neither the Waited States fiuvcrniTvcni nor an> agency thereof, nor any of their DE87 013207 emp.ojccs. makes .in} '*arr:iJiT>, ex pros or implied, or assumes unv legal liability or responsi bility fpf 'he accuracy completeness, nr usefulness of any information, apparatus, product, or protest iJistlyscd. DF represents thill its :JVU U mid not infringe privately owned rights. Refer ence herein in any sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1987
1987
1991
1991

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The study of electron temperature profile shapes, available from the multipoint Thomson scattering, ECE radiometer, and Michelson interferometer diagnostics, on TFTR has supported initial impressions that profile shapes are indeed more constant than known constraints can account for [4][5][6][7]. The shape of the profile outside approximately 0.4a (outside the sawtooth reconnection region in low q discharges) is found to be nearly invariant over a wide range of density, edge q and neutral beam heating power.…”
Section: Temperature Profile Consistencymentioning
confidence: 79%
See 2 more Smart Citations
“…The study of electron temperature profile shapes, available from the multipoint Thomson scattering, ECE radiometer, and Michelson interferometer diagnostics, on TFTR has supported initial impressions that profile shapes are indeed more constant than known constraints can account for [4][5][6][7]. The shape of the profile outside approximately 0.4a (outside the sawtooth reconnection region in low q discharges) is found to be nearly invariant over a wide range of density, edge q and neutral beam heating power.…”
Section: Temperature Profile Consistencymentioning
confidence: 79%
“…Observations on the consistency of the electron temperature profile shape (the temperature profile can vary considerably in magnitude, but it is the shape which is being studied here) have been reported on many tokamaks (TFTR, Alcator, ASDEX, JET, T-10, TEXT, etc.) [2][3][4][5][6][7][8][9][10][11][12]. In investigations of profile consistency, the profile shapes have traditionally been quantified in terms of the profile peaking parameter, T c (0)/(T e ).…”
Section: Temperature Profile Consistencymentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed that even when the heat deposition profile is widely changed in NBI [27][28][29] or ECH [30] heating experiments, the electron temperature profile does not change at all and only responds to the safety factor q(a) [27,31], while the density profile can be controlled by using pellet injection [32]. Theoretically, some explanations for this so-called profile consistency have been presented in the framework of the MHD (e.g.…”
Section: Profile Consistency For Icrf Heated Plasmasmentioning
confidence: 99%